The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/sap.0b013e3182834b63
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy and Expander-Implant Breast Reconstruction

Abstract: Our findings suggest that neither the sequencing nor timing of expander-implant exchange in the setting of PMRT affects overall complication or reconstruction failure rate. However, the timing of exchange may impact the type of complication encountered. Further investigation is necessary to determine an optimal time for expander-implant exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 16 publications
4
17
0
1
Order By: Relevance
“…4244 In a recent study, radiation therapy increased the rate of permanent implant infection and removal by approximately 5-fold compared to non-radiated breasts, similar to the odds ratio of 4 that our study observed. 45 In a separate study with a longer follow-up period, 9% of post-mastectomy irradiation patients suffered implant loss, as compared to 0.5% in the control population. 46 Radiation therapy also reduces the likelihood of implant salvage following infection or prosthesis exposure.…”
Section: Discussionmentioning
confidence: 91%
“…4244 In a recent study, radiation therapy increased the rate of permanent implant infection and removal by approximately 5-fold compared to non-radiated breasts, similar to the odds ratio of 4 that our study observed. 45 In a separate study with a longer follow-up period, 9% of post-mastectomy irradiation patients suffered implant loss, as compared to 0.5% in the control population. 46 Radiation therapy also reduces the likelihood of implant salvage following infection or prosthesis exposure.…”
Section: Discussionmentioning
confidence: 91%
“…However, the timing of the exchange after PMRT may affect the presence or type of complication that occurs. 38 Some reports reveal that delayed/2-stage, implant-based reconstruction in patients receiving radiation therapy and adjuvant chemotherapy result in fewer complications than immediate replacement of the expander. 39 In a study on the timing of implant exchange with TE and PMRT, it was found that performing implant exchange earlier after PMRT (<4 months) resulted in a higher rate of infections, whereas later exchange (>4 months) resulted in a higher rate of capsular contracture, although not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“… 39 In a study on the timing of implant exchange with TE and PMRT, it was found that performing implant exchange earlier after PMRT (<4 months) resulted in a higher rate of infections, whereas later exchange (>4 months) resulted in a higher rate of capsular contracture, although not statistically significant. 38 …”
Section: Resultsmentioning
confidence: 99%
“…Donor site morbidity is a major issue in flap procedures [28]. Capsule formation after prosthetic implants and radiotherapy-induced complications are still challenging [29, 30]. In general, autologous methods are favorable in terms of long-term stability of results.…”
Section: Discussionmentioning
confidence: 99%